The Transformation of Al-Hikam Values in Building Harmony Within a Multicultural Society in Singkawang City - Mohd Ma'shum Ahmadi; Rodi Hartono; Maskuri Maskuri; M. Djunaidi Ghony; Ari Kurniawati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the transformation of Sufi values contained in Kitab al-Ḥikam al-‘Aṭā’iyyah by Ibn ‘Aṭā’illah al-Sakandari as a spiritual foundation for fostering harmony within the multicultural society of Singkawang City. This research is motivated by the social reality of Singkawang, a city marked by ethnic, cultural, and religious pluralism, which necessitates a strong moral and spiritual basis to reinforce social cohesion. This study employs a qualitative approach within a socio-cultural framework. Data were collected through observation, interviews, and documentation, and analyzed through data condensation, display, and conclusion drawing. Kitab al-Ḥikam al-‘Aṭā’iyyah by Ibn ‘Aṭā’illah al-Iskandarī is a seminal work in Islamic mysticism that guides humans toward closeness to God while shaping noble social ethics. Values such as sincerity (ikhlāṣ), humility (tawāḍu‘), patience (ṣabr), asceticism (zuhd), and love (maḥabbah) serve as moral compasses that are highly relevant in a multicultural society like Singkawang. These teachings foster spiritual awareness that nurtures tolerance, strengthens social solidarity, and instills virtuous character in education. Al-Hikam thus becomes a source of transformative values that cultivate harmony, peace, and appreciation for diversity.